Trusting the spirit : renewal and reform in American religion - Cimino, Richard P. (Jossey-Bass, 2001)
Can renewal and reform groups rekindle spiritual vitality and fervor in today's religious institutions? The call to revive one's faith fills more pages of the Christian and Jewish scriptures than any other theme. Today, reform and renewal organizations and movements play a key role in most denominations, whether conservative, moderate, or liberal. In this fascinating book, Richard Cimino provides you with an in-depth look at six vibrant reform and renewal movements that are revitalizing traditional faith communities from the inside out.